Better clinical outcomes and lower triggering of inflammatory cytokines for allogeneic hematopoietic cell transplant recipients treated in home care versus hospital isolation – the Karolinska experience - Ringdén, Olle; Svahn, Britt-Marie; Moll, Guido; Sadeghi, Behnam (Frontiers in Immunology, 2024)
After allogeneic hematopoietic cell transplantation (Allo-HCT) and conditioning, patients are typically placed in isolated hospital rooms to prevent neutropenic infections. Since 1998, we've offered an alternative: home care for patients living within a one to two-hour drive of the hospital. This approach includes daily visits by an experienced nurse and daily phone consultations with a unit physician. When necessary, patients receive transfusions, intravenous antibiotics, and total parenteral nutrition at home. Our initial report compared 36 home care patients with 54 hospital-treated controls. Multivariate analysis showed that home care patients were discharged earlier to outpatient clinics, required fewer days of total parenteral nutrition, had less acute graft-versus-host disease (GVHD) grade II-IV, and experienced lower transplantation-related mortality (TRM) and costs. Long-term follow-up showed similar chronic GVHD and relapse rates in both groups, with improved survival rates in the home care group. A subsequent comparison of 146 home care patients with hospital-treated controls indicated that lower grades of acute GVHD (grades 0-I) were associated with home care and longer home stays. Home care was also found to be safe and beneficial for children and adolescents. Over two decades, 252 patients received home care post-Allo-HCT without any at-home fatalities. Ten-year outcomes showed a 14% TRM and a 59% survival rate. Comparing cytokine profiles, we found higher levels of GM-CSF, IFN-γ, IL-13, G-CSF, IL-5, and IL-2, and lower VEGF in hospital-treated patients, which may contribute to acute GVHD grades II-IV. A report from another center also confirmed a reduced risk of acute GVHD grades II-IV for patients treated at home [1]. In conclusion, home-based treatment following Allo-HCT yields promising outcomes.